Noncanonical amino acids: methods and protocols - Lemke, Edward A. (Methods in molecular biology, 2018)
Leveraging Formylglycine-Generating Enzyme for Production of Site-Specifically Modified Bioconjugates -- Artificial Division of Codon Boxes for Expansion of the Amino Acid Repertoire of Ribosomal Polypeptide Synthesis -- Cell-free Protein Synthesis for Multiple Site-Specific Incorporation of Noncanonical Amino Acids Using Cell Extracts from RF-1 deletion E. coli Strains -- Tub-tag Labeling; Chemoenzymatic Incorporation of Unnatural Amino Acids -- Directed Evolution of Orthogonal Pyrrolysyl-tRNA Synthetases in Escherichia coli for the Genetic Encoding of Noncanonical Amino Acids -- Genetic Code Expansion in Enteric Bacterial Pathogens -- Self-directed in Cell Production of Methionine Analogue Azidohomoalanine by Synthetic Metabolism and its Incorporation into Model Proteins -- Residue-specific Incorporation of no Canonical Amino Acids for Protein Engineering -- Using Amber and Ochre Nonsense Codons to Code Two Different Noncanonical Amino Acids in One Protein Gene -- Genetic Incorporation of Unnatural Amino Acids into Proteins of Interest in Streptomyces venezuelae ATCC 15439 -- Expression and Purification of Site-specifically Lysine-acetylated and Natively-folded Proteins for Biophysical Investigations -- Site-specific Incorporation of Sulfotyrosine Using an Expanded Genetic Code -- Site-specific Protein Labeling With Tetrazine Amino Acids -- Mapping of Protein Interfaces in Live Cells Using Genetically Encoded Crosslinkers -- Generation of Stable Amber Suppression Cell Lines -- Trapping Chromatin Interacting Proteins with Genetically Encoded, UV-Activatable Crosslinkers In Vivo -- Genetically Encoding Unnatural Amino Acids in Neurons in vitro and in the Embryonic Mouse Brain for Optical Control of Neuronal Proteins -- Genetic Code Expansion-and Click Chemistry-Based Site--Specific Protein Labelling For Intracellular DNA--PAINT Imaging -- MultiBacTAG- Genetic Code Expansion using the Baculovirus Expression System in Sf21 Cells -- Production and Chemoselective Modification of Adeno-associated Virus Site-specifically Incorporating an Unnatural Amino Acid Residue into its Capsid -- Generation of Intramolecular FRET Probes via Noncanonical Amino Acid Mutagenesis -- Fluorogenic Tetrazine--siliconrhodamine Probe for the Labeling of Non-canonical Amino Acid Tagged Proteins -- Site-specific Protein Labeling Utilizing Lipoic Acid Ligase (LplA) and Bioorthogonal Inverse Electron Demand Diels-Alder Reaction -- Genetic Encoding of Unnatural Amino Acids in C. elegans.